Obesity and febrile urinary tract infection in young children. Issue 1 (15th October 2021) - Okada, Mari; Kijima, Emi; Yamamura, Haruka; Nakatani, Hisae; Yokoyama, Haruna; Imai, Masako; Suzuki, Natsuko; Oshiba, Akihiro; Nagasawa, Masayuki
Abstract: Background: Obesity is a risk factor for infectious diseases. However, the relationship between obesity and febrile urinary tract infection (fUTI) is controversial. This study aimed to determine the relationship between obesity and fUTI in young children. Methods: We analyzed the medical records of children aged <2 years who were admitted to our hospital because of fever between April 2013 to March 2018. The children were categorized into three groups of non‐obese, overweight, and obese according to the World Health Organization weight‐for‐length curves for children aged <2 years. Results: A total of 600 patients were enrolled in this study, of whom 118 were diagnosed with first fUTI. Patients in the fUTI group were younger than those in the control group (patients who were diagnosed with other febrile diseases) (5 ± 5.11 vs 11 ± 6.53 months; P < 0.001). There were no significant differences in the populations of overweight and obese children between the fUTI and control groups. In the fUTI group, the duration of fever, types of pathogen, recurrent rate, the grades of vesicoureteral reflux, and renal scarring were not associated with obesity. The white blood cell count and C‐reactive protein levels were not significantly different among the three weight‐for‐length categories. The same results were obtained when the fUTI group was compared with an age‐matched control group ( n = 192, 4 ± 2.55 months old; P = 0.261). Conclusions: Obesity is not a significant risk factor for fUTI in febrile hospitalized young children. Our study suggests that conducting urinalysis for febrile young children without obvious sources, irrespective of obesity, should be considered.